2023
DOI: 10.1097/prs.0000000000010692
|View full text |Cite
|
Sign up to set email alerts
|

“Targeted Muscle Reinnervation at the Time of Amputation Decreases Recurrent Symptomatic Neuroma Formation”

Abstract: Background: Targeted muscle reinnervation (TMR) is an effective technique for the prevention and management of phantom limb pain (PLP) and residual limb pain (RLP) among amputees. The purpose of this study was to evaluate symptomatic neuroma recurrence and neuropathic pain outcomes between cohorts undergoing TMR at the time of amputation (ie, acute) versus TMR following symptomatic neuroma formation (ie, delayed). Methods: A cross-sectional, retrospective chart review was conducted using patients undergoing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…54 This procedure has also been associated with a lower incidence of both symptomatic neuromas and phantom limb pain compared to controls. 55 Traditional nerve management techniques prior to TMR and RPNI development included traction neurectomy, suture ligation of free nerve ends, and burial of free nerve ends into muscle…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…54 This procedure has also been associated with a lower incidence of both symptomatic neuromas and phantom limb pain compared to controls. 55 Traditional nerve management techniques prior to TMR and RPNI development included traction neurectomy, suture ligation of free nerve ends, and burial of free nerve ends into muscle…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A my Moore's peripheral nerve surgery group at The Ohio State University describes their experience using targeted muscle reinnervation (TMR) at the time of an amputation to prevent residual limb pain (RLP) from painful neuromas and phantom limb pain (PLP). 1 This "preemptive" use of TMR (early TMR) is compared with using TMR to treat existing painful neuromas in patients who previously had a limb amputation (late TMR). They concluded that both early and late TMR are effective in relieving RLP and PLP, with early TMR being significantly more effective.…”
mentioning
confidence: 99%